2008
DOI: 10.1159/000127438
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Gene Expression and Functional Activity of Ryanodine Receptors in Resistance and Conduit Pulmonary as well as Mesenteric Artery Smooth Muscle Cells

Abstract: Background: Hypoxia causes heterogeneous contractile responses in resistance and conduit pulmonary as well as systemic (mesenteric) artery smooth muscle cells (RPASMCs, CPASMCs and MASMCs), but the underlying mechanisms are largely unknown. In this study, we aimed to investigate whether the gene expression and functional activity of ryanodine receptors (RyRs) would be different in these 3 cell types. Methods: RyR mRNA expression, Ca2+ sparks and [Ca2+]i were measured by real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 87 publications
3
51
1
Order By: Relevance
“…By using real-time quantitative RT-PCR, we showed that RyR1, RyR2, and RyR3 are all expressed in freshly isolated rat and mouse PASMCs (121,122). In support of our findings, other investigators reported that all three RyR subtype mRNAs are …”
Section: Contribution Of Ryanodine Receptors= Ca 2þ Release Channelssupporting
confidence: 89%
“…By using real-time quantitative RT-PCR, we showed that RyR1, RyR2, and RyR3 are all expressed in freshly isolated rat and mouse PASMCs (121,122). In support of our findings, other investigators reported that all three RyR subtype mRNAs are …”
Section: Contribution Of Ryanodine Receptors= Ca 2þ Release Channelssupporting
confidence: 89%
“…Consistent with others' reports, our results showed that RyR-mediated Ca 2+ release is over-activated in hypoxic VSMCs, which might be owing to the increased expression of RyR and the increased sensitivity of RyR to Ca 2+ [25,26] . Furthermore, the over-activation of RyRmediated Ca 2+ release is closely associated with the occurrence of vascular hyporeactivity to NE in hemorrhagic shock rats.…”
Section: Discussionsupporting
confidence: 92%
“…CD38 activation mobilizes intracellular Ca 21 through cADPR-dependent Ca 21 release from RyR-gated stores and NAADP-dependent Ca 21 release from the acidic endo-lysosomes. Previous work by our and other laboratories have identified all three RyR subtypes in PASMCs, with RyR2 being the most abundant subtype (23,39). RyR1 and RyR2 are associated mainly with SR in the subsarcolemmal region, whereas RyR3 is localized predominantly in the perinuclear SR (23,40 There is substantial evidence suggesting that Ang II enhances ROS production through activation of NOX, contributing to Ca 21 response in VSMCs (17).…”
Section: Discussionmentioning
confidence: 87%